Usefulness of septal thickness measurement on endoscopic ultrasound as a predictor of malignancy of branched‐duct and mixed‐type intraductal papillary mucinous neoplasm of the pancreas. Issue 6 (29th April 2019) - Iwaya, Hiromichi; Hijioka, Susumu; Mizuno, Nobumasa; Kuwahara, Takamichi; Okuno, Nozomi; Tajika, Masahiro; Tanaka, Tsutomu; Ishihara, Makoto; Hirayama, Yutaka; Onishi, Sachiyo; Ito, Ayako; Kuraoka, Naosuke; et al.
Abstract : Background and Aim: Septal thickness (ST) can predict a malignant branch‐duct (BD) and mixed‐type intraductal papillary mucinous neoplasm (IPMN) of the pancreas, but its cut‐off value has not been established. The aim of the present study was to determine the optimal ST cut‐off value to predict malignancy using endoscopic ultrasound (EUS). Methods: We retrospectively identified 200 patients with IPMN, including 132 with BD‐ and mixed‐IPMN, who underwent surgical resection between 1989 and 2017. ST was defined as the septum or lesion wall with the maximum diameter in BD‐ and mixed‐IPMN. The possibility of ST as a malignant predictor was examined, as well as the diagnostic ability of ST combined with mural nodule (MN) height for malignant IPMN. Results: Among the 132 IPMN patients, pathological diagnosis was benign in 81 (61.4%) and malignant in 51 (38.6%). Area under the curve for the diagnosis of malignancy using ST was 0.74 for pathological specimens, 0.70 for EUS and 0.56 for computed tomography. Multivariate analysis showed that the odds ratios for ST ≥2.5 mm and MN height ≥5 mm were 3.51 [95% confidence interval (CI), 1.55–7.97, P = 0.003] and 3.36 (95% CI, 1.52–7.45, P = 0.003), respectively. Conclusions: Septal thickness was an independent predictive factor similar to MN height for malignant IPMN in a multivariate analysis. The ST on EUS appeared to be the thickness of a fibrotic septum associated with the malignant transformation of IPMN. An ST cut‐off value of 2.5 mm might provide an accurate prediction of malignant IPMN.